Efficacy of Tai Chi on lower limb function of Parkinson’s disease patients: A systematic review and meta-analysis - Zhu, Ping-an; Lu, Qi-qi; Li, Zhi-liang; Hu, Rong-liang; Xu, Shu; Brodersen, Lisa; Liu, Yuan-xin; Liu, Howe; Bao, Xiao (Frontiers in Aging Neuroscience, 2023)
Abstract Background: At present, the effect of Tai Chi (TC) on lower limb function in patients with Parkinson's disease (PD) is controversial. Therefore, we conducted a meta-analysis on the influence of TC on lower limb function in PD patients. Methods: According to the PRISMA guidelines, seven databases were searched. Randomized controlled trials (RCTS) were selected and screened according to inclusion and exclusion criteria. We assessed the quality of the studies using the Cochrane Risk of Bias tool and then extracted the characteristics of the included studies. The random effect model was adopted, and heterogeneity was measured by I2 statistic. Results: A total of 441 articles were screened, and 10 high-quality RCTs were with a total of 532 patients with PD met our inclusion criteria. Meta-analysis showed that compared to control groups TC improved several outcomes. TC significantly improved motor function (SMD= -0.70; 95%CI =-0.95, -0.45; P<0.001; I²=35%), although the results were not statistically significant for the subgroup analysis of TC duration (SMD= -0.70; 95%CI=-0.95, -0.45; P=0.88; I²=0%;). TC significantly improved balance function (SMD= 0.89; 95%CI=0.51, 1.27; P<0.001; I²=54%), functional walking capacity (SMD=-1.24; 95%CI = -2.40, -0.09; P= 0.04; I²=95%), and gait velocity (SMD=0.48; 95%CI= -0.02, 0.94; P=0.04; I²=78%), but did not improve endurance (SMD = 0.31; 95%CI= -0.12, 0.75; P=0.16; I²=0%), step length (SMD = 0.01; 95%CI= -0.34, 0.37; P=0.94; I²=29%), and cadence (SMD = 0.06; 95%CI= -0.25, 0.36; P=0.70; I²=0%). Conclusion: TC has beneficial effects on motor function, balance function, functional walking ability, and gait velocity, but does not improve walking endurance, stride length, and cadence.